Human centromedian-parafascicular complex signals sensory cues for goal-oriented behavior selection - Schepers, Inga M.; Beck, Anne-Kathrin; Bräuer, Susann; Schwabe, Kerstin; Abdallat, Mahmoud; Sandmann, Pascale; Dengler, Reinhard; Rieger, Jochem W.; Krauss, Joachim K. (NeuroImage (Orlando, Fla.), 2017)
Experimental research has shown that the centromedian-parafascicular complex (CM-Pf) of the intralaminar thalamus is activated in attentional orienting and processing of behaviorally relevant stimuli. These observations resulted in the hypothesis that the CM-Pf plays a pivotal role in goal-oriented behavior selection. We here set out to test this hypothesis with electrophysiological recordings from patients with electrodes implanted in CM-Pf for deep brain stimulation (DBS) treatment of chronic neuropathic pain. Six patients participated in (1) an auditory three-class oddball experiment, which required a button press to target tones, but not to standard and deviant tones and in (2) a multi-speaker experiment with a target word that required attention selection and a target image that required response selection. Subjects showed transient neural responses (8–15Hz) to the target tone and the target word. Two subjects additionally showed transient neural responses (15–25Hz) to the target image. All sensory target stimuli were related to an internal goal and required a behavior selection (attention selection, response selection). In group analyses, neural responses were greater to target tones than deviant and standard tones and to target words than other task-relevant words that did not require attention selection. The transient neural responses occurred after the target stimuli but prior to the overt behavioral response. Our results demonstrate that in human subjects the CM-Pf is involved in signaling sensory inputs related to goal-oriented selection of behavior. •Recordings from human thalamic CM-Pf during auditory oddball and multi-speaker task•Neural responses in alpha/beta range to target tone, target word and target image•Greater responses to target tone and target word compared to other task events•Neural responses occur after target stimulus onset but before overt motor response